If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+3)+9=6x-3(-5+x)
We move all terms to the left:
3(x+3)+9-(6x-3(-5+x))=0
We add all the numbers together, and all the variables
3(x+3)-(6x-3(x-5))+9=0
We multiply parentheses
3x-(6x-3(x-5))+9+9=0
We calculate terms in parentheses: -(6x-3(x-5)), so:We add all the numbers together, and all the variables
6x-3(x-5)
We multiply parentheses
6x-3x+15
We add all the numbers together, and all the variables
3x+15
Back to the equation:
-(3x+15)
3x-(3x+15)+18=0
We get rid of parentheses
3x-3x-15+18=0
We add all the numbers together, and all the variables
3!=0
There is no solution for this equation
| 2/3y-1/5=3/4 | | -3(-7u+1)-9u=2(u-5)-1 | | −31 =4j −310 | | -n+12-4n=-33 | | 13=h/3-4 | | 43.2n=-2.8 | | -1/3w+6-1=2 | | 2(x-3)+8=4x-2(-1+x) | | 1=2d-19 | | 6/h −1=−3 | | 2/8t=12/25 | | (9x-11)+(5x+17)=180 | | 4m-20=6m-6 | | ⅖(x-3)=30 | | 3(3x+7)+21=200 | | 1/3(n+2)=7 | | 19+3x^2=100+2x^2 | | 5(x+2)-8x=-34 | | 5y-9=31-y | | 6r+2+r=-12 | | 6/3=3/x | | z4+3z2-6z+10=0 | | 8p-18=-2 | | -5+6(1+7x)=-167 | | 4(y+5)=-4 | | 10=p/12 | | -22+6n=6(n-6)+6 | | b-76=18 | | 8d+4d+d+5=3d | | 76-b=18 | | -7p-4=10 | | x2–8x+16=36 |